Menentukan Nilai Prioritas Dengan Metode Analytical Hierarchy Process Untuk Menentukan Kualitas Kayu Manis Pada Bahan Arang Sebagai Alternatif Pengganti Minyak Tanah - Andi Supriadi Chan (Computer Based Information System Journal, 2015)
Cinnamon commodity is one of considerable agricultural products which is cultivated in the area of ​​West Sumatra. To increase the value, it is needed to select the product by developing the other forms of of cinnamon. It is named charcoal cinnamon. This charcoal cinnamon can be used as an alternative energy source. In order to produce good quality charcoal, it is needed the raw material selection techniques that required good cinnamon as well. There are large number of criteria in determining the cinnamon quality, it is necessary to use mathematical calculations by using AHP method. On this method, the weights initial value of the competent experts is needed. By using Decision Support System, the writer wants to test and analyze the Decision Support in determining the quality of cinnamon as charcoal material. On the methods those are provided on this system, it is suitable to solve the problems. For this reason, the author will assist in determining the quality of cinnamon as charcoal using AHP and Expert Choice application to determine the priorities value.